Nigerian capital market and the globalisation challenges : proceedings of the First Annual National Capital Market Conference - Ndanusa, Suleyman A.; Ezenwe, Uka.; Nigeria (Lagos : Securities and Exchange Commission, 2003)
The book is the Securities and Exchange Commission's reaction to changes in practices and procedures arising from the challenges of globalisation, internationalisation and developments in electronic commerce and information technology.
"Macmillan Nigeria Publishers."
Includes bibliographical references and index.
oif 11/07/14, rua 09/06/15
Loans
Keywords: Capital market; Stock exchanges; Globalization challenges